Expresión xy∨!x(y∨xz)!(x(!y∨z)vyz)
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
(x∧(z∨¬y))∨(y∧z)=(x∧¬y)∨(y∧z)¬((x∧(z∨¬y))∨(y∧z))=(y∧¬z)∨(¬x∧¬y)¬x∧¬((x∧(z∨¬y))∨(y∧z))∧(y∨(x∧z))=y∧¬x∧¬z(x∧y)∨(¬x∧¬((x∧(z∨¬y))∨(y∧z))∧(y∨(x∧z)))=y∧(x∨¬z)
y∧(x∨¬z)
Tabla de verdad
+---+---+---+--------+
| x | y | z | result |
+===+===+===+========+
| 0 | 0 | 0 | 0 |
+---+---+---+--------+
| 0 | 0 | 1 | 0 |
+---+---+---+--------+
| 0 | 1 | 0 | 1 |
+---+---+---+--------+
| 0 | 1 | 1 | 0 |
+---+---+---+--------+
| 1 | 0 | 0 | 0 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 1 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+
Ya está reducido a FNC
y∧(x∨¬z)
y∧(x∨¬z)
(x∧y)∨(y∧¬z)
(x∧y)∨(y∧¬z)